2018
DOI: 10.22146/jpki.35544
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Use of MCQ as an Assessment Method in a Medical School for Assessing Medical Students in the Competence-Based Curriculum

Abstract: Background: Student’s cognitive ability could be assessed using MCQ. The aim of this study was to evaluate the quality of MCQ as an assessment method in Medical Faculty of Muhammadiyah University Palembang. Method: This study was designed as a cross sectional descriptive observational study. Sample was MCQ assessment in Genetics and Molecular Biology Module for academic year 2013/2014 until 2015/2016 for total 299 questions. Item analysis was done manually.Results: The item analysis showed that 61.2% questions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Another research found by Purwoko and Mundijo (2018) was in line with aforementioned studies above. They carried out the research focused on the medical students in Indonesia.…”
Section: Introductionsupporting
confidence: 88%
“…Another research found by Purwoko and Mundijo (2018) was in line with aforementioned studies above. They carried out the research focused on the medical students in Indonesia.…”
Section: Introductionsupporting
confidence: 88%
“…(1) Furthermore, the enlightening changes in our understanding of how learning itself works have motivated the medical fraternity across the globe to explore techniques such as Self Directed Learning (SDL), Problem Based Learning (PBL), and Objective Assessment via Single Option Correct -Multiple Option Questions (SOC-MCQs) in the last few years. (2)(3)(4)(5). Learning augmented with such methods has consistently been more effective than traditional methods.…”
Section: Introductionmentioning
confidence: 99%